INOVASI BAGGAGE HANDLING SYSTEM DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI BALI - Eka Tampubolon, Jimmy Yan; Suryanata, I.G.N. Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.04.TAHUN.2022DO - 10.24843/EEB.2022.v11.i04.p03, 2022)
This research aims to find out and examine intensely how passenger perceived quality service of baggage handling at I GUSTI NGURAH RAI AIRPORT. This research used qualitative method with research subject namely Passenger of International I Gusti Ngurah Rai Airport. Data’s collection technique was performed with in-depth interview. The researcher used Zeithaml and Bitner servqual technique theory. The result of data analysis in this research indicates that the service quality of the baggage handling system (BHS) in the tangible aspect is considered quite good, but in the aspects of reliability, responsiveness, assurance, and empathy, it requires to enhance customer satisfaction in order to improve quality service at I Gusti Ngurah Rai Airport